KEEFEKTIFAN LAMAN INTERAKTIF DALAM MENINGKATKAN KEMAMPUAN MEMBACA INTENSIF MAHASISWA BIPA LEVEL 2 DI UNIVERSITAS NEGERI SURABAYA: Keefektifan Laman Interaktif Dalam Meningkatkan Kemampuan Membaca Intensif Mahasiswa BIPA Level 2 Di Universitas Negeri Surabaya - Alfarobby, Mufti; Suyatno, Suyatno; Sodiq, Syamsul (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
This research aims to describe the effectiveness of the interactive page "Cerita Kita" to improve the intensive reading skills of BIPA students at Surabaya State University. The learning product used is an interactive website page that can make it easier for BIPA students to access reading learning. The results of this development were tested in learning in the ISS BIPA class at Surabaya State University. The development model used is the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model to determine the effectiveness of interactive pages. This research uses a quantitative approach with data collection methods using observation sheets, interviews, and questionnaires. The subjects in this research were BIPA level 2 students at Surabaya State University. In line with the objectives, the research results show the effectiveness of the page based on observations of student activities (80%) and the completion of learning outcomes in the very good category (100%), BIPA students showed a positive response to the interactive page with a percentage of 96.9%. Key Words: Website, intensive reading, BIPA.